2017
DOI: 10.1101/203000
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Antiviral and Cancer Genomic DNA Deaminase APOBEC3H Is Regulated by a RNA-Mediated Dimerization Mechanism

Abstract: SUMMARY

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 80 publications
2
37
0
Order By: Relevance
“…A third consideration could be negative interference by an as yet unidentified factor. For instance, both intra/inter-A3 oligomerization and RNA binding are known to inhibit the activity of multiple A3 family DNA deaminases including A3B and A3H (Cortez et al, 2019;Shaban et al, 2018). However, these considerations are tempered by the fact that our original human A3B 5 transgenic line was lost early in these studies likely due to its exerting negative selective pressure and catalyzing self-inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…A third consideration could be negative interference by an as yet unidentified factor. For instance, both intra/inter-A3 oligomerization and RNA binding are known to inhibit the activity of multiple A3 family DNA deaminases including A3B and A3H (Cortez et al, 2019;Shaban et al, 2018). However, these considerations are tempered by the fact that our original human A3B 5 transgenic line was lost early in these studies likely due to its exerting negative selective pressure and catalyzing self-inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that A3H variants expressing the R105G and N15del mutations may share a common negative regulatory mechanism that affects the stability and localization of these mutants, and the N15del mutation leads to greater utilization of this mechanism. Several groups have recently described the mechanism by which stable A3H dimerizes through its interaction with duplex RNA, and this complex is maintained primarily through protein-RNA contacts [23,[25][26][27]. Interaction with duplex RNA is mediated by aromatic and positively-charged residues in Loop 1, Loop 7, and the C-terminal a6 helix [23,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Recent structural studies of pig-tailed macaque [23], human [24,25], and chimpanzee [26] A3H have established a unique RNA interaction mechanism central to the antiviral function of A3H. Two A3H monomers interact with opposite sides of a short RNA duplex, and the A3H monomers in this complex interact primarily with the RNA duplex and not with one another.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, A3H is polymorphic in human populations like A3C, however, A3H haplotype II confers strong antiviral activity (25). Recent structural work has shown that A3H binds to RNA to make functional dimers (3537). This suggests that perhaps A3H evolved an independent mechanism to form higher-order structures that is dependent on RNA, but that A3C is unable to do this unless the second cytidine deaminase domain is artificially engineered.…”
Section: Discussionmentioning
confidence: 99%